Dead med - McFadden, Freida ([Freida McFadden], 2024)
"When Heather McKinley dreamed of becoming a doctor, she imagined curing sick kids and sporting pink stethoscopes. She never anticipated the sleepless nights, grueling exams, and endless labs. And she certainly never knew that her medical school earned the nickname Dead Med thanks to the tragic history of students overdosing on illegal drugs. But Heather would never consider doing anything like that. That is, until her longtime boyfriend dumps her, she finds herself failing anatomy, and her world starts to crumble. Then, on the night before the final exam in anatomy, a shot rings out through the hallways of Dead Med. The school has claimed yet another casualty. One of Heather's classmates has done the unthinkable, and before her desperate 911 call even connects, it will happen again" -- Amazon.com.